Answers

The Brainliest Answer!
  • qais
  • Content Quality
2016-01-20T11:49:14+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
α and β are roots, then equation is (x -α)(x -β)=0
so,if c and d are roots, then equation will be  (x -c)(x -d)=0
but,here c and d are roots of the equation (x -a)(x -b) -k =0
so, (x -c)(x -d)= (x -a)(x -b) -k 
⇒(x -c)(x -d) + k = (x -a)(x -b)_______(1)
∵  a and b are roots of equation (x -a)(x -b)=0 
and from equation (1) 
(x -c)(x -d) + k = (x -a)(x -b)
hence , a and b are roots of equation (x -c)(x -d) + k =0
1 5 1